2021
DOI: 10.1038/s41598-021-89838-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum entanglement and statistics of photons on a beam splitter in the form of coupled waveguides

Abstract: It is well known that a beam splitter (BS) can be used as a source of photon quantum entanglement. This is due to the fact that the statistics of photons changes at the output ports of the BS. Usually, quantum entanglement and photon statistics take into account the constancy of the reflection coefficient R or the transmission coefficient T of the BS, where $$R + T = 1$$ R + T = 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In the case of constants R and T , quantum entanglement is a periodic function contingent on , and for large a rapidly oscillating dependence, which is a negative factor for use in quantum technologies. It should be added that in [ 21 ] the simplest case of input states was analyzed in detail and it was shown that quantum entanglement and photon statistics, at the BS output ports, can be very different for non-monochromatic photons compared with monochromatic photons. In this paper a similar conclusion is drawn, but in the general case, not limited to states.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of constants R and T , quantum entanglement is a periodic function contingent on , and for large a rapidly oscillating dependence, which is a negative factor for use in quantum technologies. It should be added that in [ 21 ] the simplest case of input states was analyzed in detail and it was shown that quantum entanglement and photon statistics, at the BS output ports, can be very different for non-monochromatic photons compared with monochromatic photons. In this paper a similar conclusion is drawn, but in the general case, not limited to states.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Let us choose von Neumann entropy as a measure of quantum entanglement. It is well known [ 20 , 21 , 24 , 25 , 26 ] that in this case the entropy will be .…”
Section: Quantum Entanglement Of Monochromatic Photonsmentioning
confidence: 99%
See 3 more Smart Citations